Antenatal care utilisation and receipt of its components in Nigeria: Assessing disparities between rural and urban areas—A nationwide population-based study - Adewuyi, Emmanuel; Auta, A.; Adewuyi, M.I.; Philip, A.A.; Olutuase, V.; Zhao, Yun; Khanal, V. (2024)
Introduction Antenatal care (ANC) is crucial for positive pregnancy outcomes, but it is underutilised in Nigeria, suggesting unmet needs, and potentially contributing to the country’s high burden of maternal and neonatal mortalities. This study comprehensively assesses ANC utilisation and receipt of its components in Nigeria, focusing on disparities between rural and urban areas. Methods We used the data disaggregation approach to analyse the Nigeria Demographic and Health Survey 2018. We estimated ANC utilisation, assessed the receipt of ANC components, and identified factors associated with eight or more (≥ 8) ANC contacts nationally and across rural and urban residences. Results Nationwide, only 20.3% of women had ≥ 8 ANC contacts, with a significant disparity (P < 0.001) between urban (35.5%) and rural (10.4%) areas in Nigeria. The North-East region had the lowest ANC utilisation nationally (3.7%) and in urban areas (3.0%), while the NorthWest had the lowest in rural areas (2.7%). Nationally, 69% of mothers received iron supplements, 70% had tetanus injections, and 16% received medicines for intestinal parasites, with urban residents having higher proportions across all ANC components. Maternal and husband education, health insurance, and maternal autonomy were associated with increased ANC odds at the national, rural, and urban residences. However, differences exist, with all ethnicities having higher ANC odds than the Hausa/Fulanis in urban areas and the Yorubas demonstrating greater odds than other ethnicities in rural settings. Internet use was significant only in the national context, watching television only in urban settings, while maternal working status, wealth, birth type, religion, and radio listenership were significant in rural areas. Conclusion Our study reveals significant disparities in ANC utilisation and components across Nigeria, with rural residents, particularly in northern regions, as well as socioeconomically disadvantaged and teenage mothers facing notable challenges. A multifaceted approach prioritising the interplay of intersectional factors like geography, socioeconomic status, education, religion, ethnicity, and gender dynamics is essential. Key strategies should include targeted interventions to promote educational opportunities, expand health insurance coverage, leverage internet and context-specific media, and foster socioeconomic empowerment, with priority for underserved populations.